Sins of the flesh - McCullough, Colleen, 1937-2015 (McCullough, Colleen, 1937-2015. Carmine Delmonico novel, 2013)
"It's August 1969 in the sleepy college town of Holloman, Connecticut, and police Captain Carmine Delmonico is away on vacation. Back at home, first one, then two anonymous male corpses turn up--emaciated and emasculated. Sergeant Delia Carstairs and Lieutenant Abe Goldberg connect the victims to four other bodies, and suddenly they realize Holloman has a psychopathic killer on the loose. Luckily Carmine decides to come back from vacation early. Carmine's team begins to circle a trio of eccentrics living on a beautiful estate; they readily admit to knowing all the victims, but their stories keep changing. They share a dark past, family ties, and painful memories. One of them is a woman who has recently become a friend of Delia's, along with another woman who is the respected head of the insane asylum. She has done groundbreaking work rehabilitating one very difficult patient who is now her most trusted assistant. The three women met while rescuing a cat from a tree, and now they find they share a love of intelligent conversation and their enjoyment of living the single life. When a gas station attendant is viciously murdered, and then Carmine barely escapes being next in the body count, it becomes apparent that Holloman has two killers at large with two completely different modus operandi. Suddenly the summer isn't so sleepy any more"--